Which Taxa Are Alien? Criteria, Applications, and Uncertainties. (7th July 2018) - Essl, Franz; Bacher, Sven; Genovesi, Piero; Hulme, Philip E; Jeschke, Jonathan M; Katsanevakis, Stelios; Kowarik, Ingo; Kühn, Ingolf; Pyšek, Petr; Rabitsch, Wolfgang; Schindler, Stefan; van Kleunen, Mark; et al.
Abstract: Human activities such as the transport of species to new regions and modifications of the environment are increasingly reshaping the distribution of biota. Accordingly, developing robust, repeatable, and consistent definitions of alien species that serve scientific and policy purposes has become of prime importance. We provide a set of classification criteria that are widely applicable across taxa and realms and offer guidance on their use in practice. The criteria focus on (a) acknowledging the role of assessment uncertainty, (b) incorporating time since introduction, (c) considering infraspecific taxonomic ranks, and (d) differentiating between alien species whose survival depends on explicit human assistance from those that survive without such assistance. Furthermore, we make recommendations for reducing assessment uncertainty, suggest thresholds for species assessment, and develop an assessment scheme. We illustrate the application of the assessment criteria with case studies. Finally, the implications for alien species management, policy, and research are discussed.